2015
DOI: 10.1074/jbc.m115.639468
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Elongates Hypothalamic Neuronal Cilia via Transcriptional Regulation and Actin Destabilization

Abstract: Background:The primary cilia in hypothalamic neurons are important for sensing metabolic signals. Results: Leptin promotes cilium growth in the hypothalamic neuronal cells by increasing intraflagellar transport gene transcription and F-actin rearrangement. Conclusion: Leptin is an important regulator of ciliary length in hypothalamic neurons. Significance: Dynamic regulation of hypothalamic neuron ciliary lengths represents a novel strategy by which leptin regulates energy balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…At the same time, insulin treatment also lengthened cilia on N1 hypothalamic neuronal cultures, albeit at very high concentrations (30–50 nM insulin) that exceed the physiological range. A subsequent report demonstrated that leptin treatment increased regulatory factor X1 (Rfx1)‐dependent transcriptional activation of core ciliary components Kif3a and Ift88 and thus elongated primary cilia in the hypothalamus . Because N1 hypothalamic neuronal cells overexpressing either phosphatase and tensin homolog (PTEN) or glycogen synthase kinase 3β (GSK3β) showed reduced binding of Rfx1 to the Kif3a promoter compared with controls, leptin and PTEN–GSK3β signaling might regulate the expression of IFT protein via modulation of Rfx1 binding …”
Section: Ciliary Function and Leptin Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, insulin treatment also lengthened cilia on N1 hypothalamic neuronal cultures, albeit at very high concentrations (30–50 nM insulin) that exceed the physiological range. A subsequent report demonstrated that leptin treatment increased regulatory factor X1 (Rfx1)‐dependent transcriptional activation of core ciliary components Kif3a and Ift88 and thus elongated primary cilia in the hypothalamus . Because N1 hypothalamic neuronal cells overexpressing either phosphatase and tensin homolog (PTEN) or glycogen synthase kinase 3β (GSK3β) showed reduced binding of Rfx1 to the Kif3a promoter compared with controls, leptin and PTEN–GSK3β signaling might regulate the expression of IFT protein via modulation of Rfx1 binding …”
Section: Ciliary Function and Leptin Signalingmentioning
confidence: 99%
“…A subsequent report demonstrated that leptin treatment increased regulatory factor X1 (Rfx1)-dependent transcriptional activation of core ciliary components Kif3a and Ift88 and thus elongated primary cilia in the hypothalamus. 59 Because N1 hypothalamic neuronal cells overexpressing either phosphatase and tensin homolog (PTEN) or glycogen synthase kinase 3␤ (GSK3␤) showed reduced binding of Rfx1 to the Kif3a promoter compared with controls, leptin and PTEN-GSK3␤ signaling might regulate the expression of IFT protein via modulation of Rfx1 binding. 59 All of the above lines of evidence point to defective leptin signaling as a direct cause of the obesity phenotype observed in metabolic ciliopathies such as BBS.…”
Section: Ciliary Function and Leptin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin-myosinmediated contraction participates in ciliary abscission as the neuronal differentiation program is triggered (Das and Storey, 2014). Leptin elongates hypothalamic cilia via transcriptional regulation and actin destabilization (Kang et al, 2015), whereas the microRNA miR-129-3p regulates cilia assembly through the concomitant transcriptional silencing of centrosomal proteins and repression of actin filament formation (Cao et al, 2012). Altogether, these findings highlight the existence of concurrent regulatory mechanisms coordinating ciliogenesis, actin dynamics, and transcription.…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, these results might be indicating that while leptin signaling defects do play an important role in the development of obesity in BBS and other ciliopathies, mechanisms that are still unknown might be important to initiate the process. Interestingly, the functional relationship between leptin and cilia appears to be even more complex as a recent work reports on leptin regulating cilia assembly and ciliary length by destabilizing actin filaments and increasing intraflagellar transport proteins through gene transcription regulation [126,127]. Therefore, leptin could modulate cilia length and the sensitivity of hypothalamic neuronal cilia to metabolic signals.…”
Section: A Neuroendocrine Origin For Obesity In Bbsmentioning
confidence: 99%